Gender, sex, and sexuality among contemporary youth : Generation Sex - Claster, Patricia Neff.; Blair, Sampson Lee. (Bingley : Emerald Publishing Limited, 2017)
This volume examines the evolving norms concerning sex, gender, and sexuality in the lives of children and adolescents addressing topics such as: the development of gender identity, sexual behavior among youth, LGBT youth, transgendered youth, parental and peer influences upon the development of gender and gender identity and dating violence.
1, 'Dare to be Different': How Religious Groups Frame and Enact Appropriate Sexuality and Gender Norms among Young Adults; Rhys H. Williams, Courtney Ann Irby and R. Stephen Warner 2, Estimating the Status and Needs of Homeless LGBT Adolescents: Advocacy, Identity, and the Dialectics of Support; Timothy Stablein 3, The Intersex Kids Are All Right? Diagnosis Disclosure and the Experiences of Intersex Youth; Georgiann Davis and Chris Wakefield 4, Examining the Family Transition: How Parents of Gender-Diverse Youth Develop Trans-Affirming Attitudes; Krysti N. Ryan 5, Let's Talk about Sex for Money: An Exploration of Economically Motivated Relationships among Young, Black Women in Canada; Ciann Wilson and Sarah Flicker 6, Educational Attainment and Sexual Orientation in Adolescent and Young Adult Males; Mollie T. McQuillan 7, 'To Feel Him Love Me': Emerging Intersections of Identity, Queerness and Differing Ability; Rebecca G. Harvey, Paul D. Levatino and Julie A. Liefeld 8, Sexual Debut Education: Cultivating A Healthy Approach to Young People's Sexual Experiences; Yvonne Vissing 9, Breaking Up is Hard to Do: Teen Dating Violence Victims' Responses to Partner Suicidal Ideation; Jessica M. Fitzpatrick 10, Two by Two: Heteronormativity and the Noah Story for Children; Sarah M. Corse.
Print version record.
eBooks on EBSCOhost
Keywords: Gender identity; Gender expression; Sex role; Children -- Sexual behavior; Teenagers -- Sexual behavior; Identité de genre; Expression de l'identité de genre; Rôle selon le sexe; Enfants -- Sexualité.; Adolescents -- Sexualité.; sex role; SOCIAL SCIENCE -- Gender Studies; Children -- Sexual behavior; Gender expression; Gender identity; Sex role; Teenagers -- Sexual behavior